Double-pore structure porous Mo–Si–B intermetallics fabricated by elemental powder metallurgy method using NH4HCO3 as pore-forming agent - Yongan Huang; Laiqi Zhang; Shizhong Wei (Materials Research Express, 2020)
The multiphase porous intermetallic compounds Mo _3 Si-Mo _5 Si _3 -Mo _5 SiB _2 of a double-pore structure has been successfully fabricated by combining the in situ reaction synthesis with the pore-forming agent method. The effects of NH _4 HCO _3 content and size on porosity, pore diameter distribution, permeability, and compressive strength were investigated systematically. The results show that: with the NH _4 HCO _3 increasing from 0 to 60 vol%, the total porosity increases from 46.6% to 73.2%, the big pores volume increases from 2.3% to 69.4%, the gas permeability increases from 5.34 × 10 ^−7 l/(min · cm ^2  · Pa) to 1.74 × 10 ^−4 l/(min · cm ^2  · Pa), and the compressive strength decreases from 392 MPa to 14.8 MPa; on the other side, with the NH _4 HCO _3 size increased from 48 μ m to 230 μ m, the parameters of this porous intermetallics changed slightly except to the significant increase of big pores diameter. An exponential equation of σ _c  =  σ _s (1- ρ ) ^1/0.254 based on generalized mixture rule (GMR) has been put forward to quantitatively describe porosity-compressive strength behaviors. Results from this study indicate the potential applications in various filtration environments by tailoring the shape, contents, and size of the pore-forming agent.